Detection of Small‐Molecule Aggregation with High‐Throughput Microplate Biophysical Methods. Issue 1 (9th March 2020) - Allen, Samantha J.; Dower, Corey M.; Liu, Annie X.; Lumb, Kevin J.
Abstract: Small‐molecule drug discovery can be hindered by the formation of aggregates that act as non‐selective inhibitors of drug targets. Such aggregates appear as false positives in high‐throughput screening campaigns and can bedevil structure‐activity relationships during compound optimization. Protocols are described for resonant waveguide grating (RWG) and dynamic light scattering (DLS) as microplate‐based high‐throughput approaches to identify compound aggregation. Resonant waveguide grating and dynamic light scattering give equivalent results for the compound test set, as assessed with Bland‐Altman analysis. © 2019 The Authors. Basic Protocol 1 : Resonant waveguide grating (RWG) in 384‐well or 1536‐well plate format to detect compound aggregation Basic Protocol 2 : Dynamic light scattering (DLS) in 384‐well plate format to detect compound aggregation